2019
DOI: 10.1016/j.celrep.2019.11.114
|View full text |Cite
|
Sign up to set email alerts
|

PCNA Unloading Is Negatively Regulated by BET Proteins

Abstract: Highlights d ATAD5 and BRD4 are enriched on nascent DNA d A conserved region upstream of ATAD5 PCNA-unloading domain binds to BRD4 ET domain d Acetyl-histone-bound BRD4 inhibits PCNA unloading by ATAD5-RLC on nascent DNA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Indeed, BET inhibition has resulted in DNA replication stress (Bowry et al, 2018) and replication re-initiation (Zhang et al, 2018). BET proteins are also implicated in the regulation of proliferating cell nuclear antigen unloading (Kang et al, 2019). The SWAN analysis presented here underscores the importance of BET proteins in the biology of DNA replication and serves as an example of SWAN usage outside of cancer genetics.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, BET inhibition has resulted in DNA replication stress (Bowry et al, 2018) and replication re-initiation (Zhang et al, 2018). BET proteins are also implicated in the regulation of proliferating cell nuclear antigen unloading (Kang et al, 2019). The SWAN analysis presented here underscores the importance of BET proteins in the biology of DNA replication and serves as an example of SWAN usage outside of cancer genetics.…”
Section: Resultsmentioning
confidence: 99%
“…Transcription of the reverse strand may be toxic because of collision with DNA replication, which may occur predominantly in one direction as the repeats themselves have inefficient origins of replication (12) . Intriguingly, BRD4 interacts with PCNA, which is highly enriched on the lagging strand (73) . This could account for strand specificity of BRD4-dependent transcripts, which DICER1 would normally remove from the lagging strand to avoid collisions during replication.…”
Section: Discussionmentioning
confidence: 99%
“…All the 32 homozygous mutants grew normally until 48 hpf with only four mutants showing morphological malformation and hematopoietic defects before 6 dpf, in line with observations that genomic homeostasis is linked to hematopoiesis (Botthof et al, 2017, Marsh et al, 2018, Farres et al, 2015). Mutants of pcna and atad5a , two critical genes for DNA replication (Kang et al, 2019a), showed reduced proliferation and induced apoptosis in the blood precursors at the CHT, while ddb1 homozygous mutants showed loss of HSPCs caused by reduced proliferation. PCNA and ATAD5 are critical for not only general DNA replication but also for the maintenance of replication fork stability (Park et al, 2019).…”
Section: Discussionmentioning
confidence: 99%